Dual Regulatory Governance in The Islamic Capital Market: Institutional Synergy Between Ojk and Sharia Supervisory Boards - Roni Taufik Tafakkur; Wafda Vivid Izziyana; Mutiara Apriliyani; Imam Rifan (Faculty of Law, Muhammadiyah University of Surabaya, 2025)
The rapid growth of the Indonesian Islamic capital market is constrained by institutional challenges and authority overlaps between the Financial Services Authority (OJK) as the state financial regulator and the Islamic Supervisory Board (DPS) as the Sharia authority. This study aims to analyze the scope, authority, and institutional coordination between OJK and DPS in supervising Islamic capital market activities and financial products. This study employs an empirical legal research method. The results demonstrate that while both institutions share the objective of market oversight, existing regulatory frameworks lack integrated coordination, resulting in ambiguous boundaries regarding enforcement and Sharia compliance verification. Field findings reveal that the separation of state financial supervision and religious compliance assessment frequently leads to legal uncertainty for market practitioners, creates operational inefficiencies, and causes significant delays in financial product approvals. Furthermore, the supervision of Sharia compliance remains suboptimal due to the limited executive and investigative power of the DPS compared to the binding regulatory and sanctioning authority of OJK. This structural disparity prevents proactive monitoring of ongoing market transactions, leaving Sharia enforcement vulnerable to administrative gaps. Consequently, inconsistent regulatory interpretations between state law and religious fatwas continue to emerge, weakening the overall oversight framework. This study concludes that establishing a synchronized regulatory framework, integrating Sharia oversight protocols directly into OJK digital systems, and formalizing a joint-coordination mechanism are imperative to eliminate institutional overlapping, strengthen legal certainty, enhance public trust, and foster the sustainable development of the Indonesian Islamic capital market.